Disiplinlerarası Eğitim Algısı Ölçeğinin (DEAÖ) Geçerlik ve Güvenirlik Çalışması. - TERZİOĞLU, FÜSUN; AKTAŞ, DEMET; ERTUG, NURCAN; BOZTEPE, HANDAN (Journal of Education & Research in Nursing / Hemşirelikte Eğitim ve Araştırma Dergisi, 2019)
Aim: To adapt and evaluate the validity and reliability of the Turkish version of the Interdisciplinary Education Perception Scale (IEPS-TR). Methods: The IEPS-TR was used in this methodological study to identify the perceptions of interdisciplinary education of health professionals and students working with different occupational groups. The population of the study comprised 215 university students from five different undergraduate health science programs of a university in Ankara, Turkey. The validity and reliability of the scale were assessed using exploratory factor analysis (EFA), Cronbach's alpha, and intraclass correlation coefficient (ICC). Results: As a result of the factor analysis, a seventeen-item scale with three factors was achieved. The Cronbach's alpha coefficient was found to be 0.926, and the scale was determined to be valid and reliable. Conclusion: Our study results show that the Turkish version of the IEPS is a valid and reliable instrument. The IEPS-TR can be used in measuring interdisciplinary perceptions of health care students working with different occupational groups.